ANALISIS PERBANDINGAN KINERJA KEUANGAN PT. BRI AGRO, TBK. SEBELUM DAN SESUDAH AKUISISI - Istiani, Dian Ayu; Saryadi, Saryadi; Nurseto, Sendhang (Jurnal Ilmu Administrasi Bisnis, 2014)
PT. BRI Tbk. acquired PT. Bank Agroniaga, Tbk. related to the single presence policy of Bank Indonesia. To still protect public confidence in the PT. BRI Agro, Tbk., the bank must be in good health. The purposes of this study to find out whether there are differences in the financial performance and condition the health of PT. BRI Agro Tbk. before and after the acquisition. This study only using analysis CAEL of CAMEL, because we did not analyze management. The variables are CAR, BDR, ROA, BOPO, CR and LDR. The sample is a monthly financial report of PT. BRI Agro Tbk. published by Bank Indonesia during two years before and two years after the acquisition. The method to test the hypothesis using paired sample t-test. The results showed all the variable t is greater than t table is 2.069 and health level condition t is greater than t table is 2.365. So, there are significant differences between before and after the acquisition. We recommend PT. BRI Agro,Tbk. can maintain CAR, ROA, CR, LDR, decreased BDR and improve ROA.